Change in self-efficacy as a source of state dependence in labor market dynamics? - Alexander Mosthaf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Using the PASS survey, I analyze the relationship between employment and self-efficacy. Estimating a dynamic model which takes into account reverse causality and selection on unobservables, I show that employment positively affects self-efficacy and vice versa. Hence, changes in the personal trait self-efficacy may be a source of state dependence in labor market dynamics. Hence, reverse causality should be taken into account when estimating the effect of self-efficacy on labor market outcomes.
Keywords: J60; 330